A study on stress among women employees of erstwhile SBT consequent to merger with SBI. - Fathima, A V. (Post Graduate and Research Department of Commerce, Mar Thoma College Chungathara, 2024)
The Indian banking sector has experienced various modes of restructuring through merger and acquisition. Merger and acquisitions help banking sector to keep itself updated. Even though merger and acquisitions provide synergies and competitive advantages, there are several emotional, physical and survival issues related with employees. The workplace culture will change dramatically due to merger and acquisition in Kerala. This study entitled ―A study on the stress among women employees of erstwhile SBT consequent to merger with SBI‖ is an attempt to investigate the occupational stress, effects of occupational stress and mediating role of employee commitment in the relationship between job stress and employee performance of the women employees in the context of SBI-SBT merger. The study also extracted the moderating effects of measures to mitigate the stress on the effect of job stress on work engagement and job performance. The primary data has been collected by administering pre-tested questionnaires with the selected 585 women employees of SBI who were employees of SBT in the cadres of officers and award staffs (clerical cadre).One sample t test, paired sample t test, independent t test, and one-way ANOVA with Tukey's HSD post hoc analysis were used to examine the stress level, consequences and it‘s before and after merger comparison among women employees of SBI who were the employees of SBT. The Covariance Based Confirmatory Factor Analysis (CB-CFA) and Structural Equation Modeling, Mediation model and the bootstrapping approach were used.
CHAPTER I INTRODUCTION-1-22 CHAPTER 2 REVIEW OF LITERATURE 23-78 CHAPTER 3 STRESS AND MERGER IN THE BANKING SECTOR – AN OVERVIEW 79-97 CHAPTER 4 ANALYSIS AND INTERPRETATIONS 99-251 CHAPTER 5 FINDINGS AND CONCLUSION 253-26
Keywords: Banking, stress, women, SBT/SBI,family and social issues, health issues, psychological and behavioral issues.